2020
DOI: 10.3390/su12073023
|View full text |Cite
|
Sign up to set email alerts
|

Does Chinese Inward Foreign Direct Investment Improve the Productivity of Domestic Firms? Horizontal Linkages and Absorptive Capacities: Firm-Level Evidence from Ethiopia

Abstract: Publicized as a global call for action in 2015, the United Nations General Assembly (UNGA) has forwarded an agenda of resolutions to achieve the goals of sustainable development by 2030 (SDGs). Due to the specific challenges of funding gaps and the lack of advanced technology, the majority of Sub-Saharan African (SSA) countries are still behind the standard of world development. Since foreign direct investment (FDI) has the potential to bring much-needed capital and efficient technology, FDI has often been con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 57 publications
(157 reference statements)
1
9
1
Order By: Relevance
“…Economic growth literature has shown that numerous potential variables can affect A (total factor productivity). Thus, owing to the availability of data and following the researches of (Miao, Lang et al, 2020;Negash et al, 2020) to mention a few, we expressed total factor productivity as a function of China-Africa trade and China outward foreign direct investment as;…”
Section: Theoretical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Economic growth literature has shown that numerous potential variables can affect A (total factor productivity). Thus, owing to the availability of data and following the researches of (Miao, Lang et al, 2020;Negash et al, 2020) to mention a few, we expressed total factor productivity as a function of China-Africa trade and China outward foreign direct investment as;…”
Section: Theoretical Modelmentioning
confidence: 99%
“…Although there is consent on the increasing importance of China and Africa's economic partnership, there are many controversies on how it affects both sides, especially Africa's economic performance (Chen & Dollar, 2018). There are also doubts about whether China's OFDI to African countries promotes productivity growth, and technology absorption in the Africa continent (Negash et al, 2020). Further, a new strand of African economic literature questions the extent to which Africa's trade deals with China and China's OFDI to Africa seeks to satisfy a "win-win situation" as often trumpeted by China's Master Facility (Habyarimana & Opoku, 2018;Luo & Gao, 2020;Megbowon et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies Weisbrod and Whalley (2011); Doku et al (2014) and Ross (2015) conclude that Chinese OFDI had brought a positive impact on SSA countries. Negash et al (2020) also reported that Chinese firms were more productive than domestic firms in Ethiopia and their presence has also brought positive productivity spillover effects for domestic firms that can help for sustainable development. The varied results of the existing studies have evidenced the need for further research.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, previous works have also analyzed the link between globalization and either income inequality [ 75 ], labor market institutions [ 76 ], financial intermediation [ 77 ] or human development [ 78 ], among others. Recently, another interesting line of research is based on the study of the effect and conditioning factors of foreign direct investment (as a manifestation of globalization) in less developed nations, such as African countries [ 79 , 80 ]. However, the objective of this work is to analyze the association of globalization (and other macroeconomic indicators, such as public expenditures) with a representative indicator of the health status of population, such as life expectancy, in the ambit of European countries.…”
Section: Introductionmentioning
confidence: 99%